The Burden of Proof in Vietnamese Civil Procedure - Hung, Nguyen Vinh; Nguyet, Le Kim; Phuong, Ha Thi Lan (Jurnal Cita Hukum, 2026)
Currently, Vietnam is changing its judicial model. Civil procedure is becoming increasingly important. In Vietnamese civil procedure, the participated subjects’ burden of proof plays an especially important part and has great relations to the outcome of the settlement of civil cases. This is the liability that most subjects of civil procedure have to carry out; however; the burden of proof is a complicated problem and there are many limitations that make it difficult for subjects to do their bit. Due to that fact, the article studies the burden of proof in civil procedure, on that basis, proposes some solutions to contribute to improving the efficiency of the performance of the burden of proof in civil procedure in Vietnam.